Formation of free amino acids in rhizosphere and nonrhizosphere soil - Schmidt, E. L., author; Paul, Eldor A., author; Soil Science Society of America, publisher (Colorado State University. Libraries, 1961)
Untreated samples of nonrhizosphere and soybean rhizosphere soils each contained about 15 identified free amino acids totaling 2 to 4 µg. per g. of soil; lysine was the most prevalent amino acid in each preparation. Numerous additional unidentified compounds occurred at concentrations estimated as 0.1 to 0.5 µg. per g. Treatment with glucose and potassium nitrate increased the amount of free amino acids to about 100 µg. per g. after 3 days. Concentrations declined after 3 days but still were 4 to 5 times that of the untreated control after 2 weeks' incubation. Glutamic acid was the dominant amino acid in all treated soils. Rhizosphere soil did not differ quantitatively from nonrhizosphere in samples treated with glucose, although a greater variety of ninhydrin reacting compounds was encountered in rhizosphere soil. Treated soils incubated at 20% field moisture capacity differed little in free amino acids from those held at 30%. The features of the free amino acid fraction are discussed.
Keywords: extraction; ionic extractants; NH4OAc